Is There Any Opportunity to Provide an HBV Vaccine Booster Dose before Anti-Hbs Titer Vanishes? - Papadopoli, Rosa (Vaccines (Basel), 2020)
Whether the primary Hepatitis B vaccination confers lifelong protection is debated. The aim of the study was to assess the effectiveness of booster doses in mounting a protective HBV immune response in subjects vaccinated 18–20 years earlier. The study population consisted of vaccinated students attending medical and healthcare professions schools. A booster dose was offered to subjects with a <10 mIU/mL anti-HBs titer. The post-booster anti-HBs titer was evaluated after four weeks. The subjects with a <10 mIU/mL post-booster anti-HBs titer, received a second and third dose of the vaccine and after one month they were retested. A <10 mIU/mL anti-HBs titer was found in 35.1% of the participants and 92.2% of subjects that were boosted had a ≥10 mIU/mL post-booster anti-HBs titer, whereas 7.8% did not mount an anamnestic response. A low post-booster response (10–100 mIU/mL anti-HBs) was significantly more likely in subjects with a <2.00 mIU/mL pre-booster titer compared to those with a 2.00–9.99 mIU/mL pre-booster titer. The anamnestic response was significantly related to the baseline anti-HBs levels. A booster dose of the HBV vaccine may be insufficient to induce an immunological response in subjects with undetectable anti-HBs titers. A booster dose might be implemented when an anamnestic response is still present.